Controversy Surrounding the Grand Qāḍī of the Sudan, 1899 – 1956: A Historical Analysis - Abdul Hamid, Besah; Ibrahim, Hassan Ahmed (Intellectual Discourse, 2006)
Abstract: The establishment of a nominally Anglo-Egyptian partnership, but practically a defacto British rule in the Sudan, led the British to appoint Egyptians in religious posts, including the position of the Grand Qāḍī. But the British drive to de-Egyptianise the Sudan administration, and the steady rise of Sudanese nationalism led the British government, after a long acrimonious debate, to appoint a Sudanese to be the Grand Qāḍī. This move, the historical survey shows, was well received by the Sudanese ‘ulamā and the Muftī apparently went to the extent of “fabricating” religious evidence in its favour.